2014
DOI: 10.4012/dmj.2014-008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium salt of 10-methacryloyloxydecyl dihydrogen phosphate produced on the bond durability of one-step self-etch adhesive

Abstract: Five experimental 10-methacryloyloxydecyl dihydrogen phosphate (MDP)-based one-step self-etch adhesives were designed by varying amounts of MDP. The aim of this study was to examine the effect of the quantity of calcium salt of MDP (MDP-Ca) salt produced by demineralization on the bond durability between experimental one-step adhesives and enamel or dentin. Bond strengths of experimental adhesives to the enamel and dentin were measured, before and after 30,000×thermocycling. The fractured enamel and dentin sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…For the application of MDP to calcium-containing dental hard tissues, it has been shown that the amount of MDP-Ca salt produced is proportional to the concentration of MDP present in the primer solution, which, in turn, affects the bond strengths of MDP-primed enamel or dentin313233. Hence, the authors speculate that shear bond strength of methacrylate resin composites to PENTA-primed Y-TZP may be affected by the concentration of PENTA present in the experimental ceramic primer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…For the application of MDP to calcium-containing dental hard tissues, it has been shown that the amount of MDP-Ca salt produced is proportional to the concentration of MDP present in the primer solution, which, in turn, affects the bond strengths of MDP-primed enamel or dentin313233. Hence, the authors speculate that shear bond strength of methacrylate resin composites to PENTA-primed Y-TZP may be affected by the concentration of PENTA present in the experimental ceramic primer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshihara et al 16) first reported the characteristic of self-assembled nanolayering structures at the adhesive interface, which result from the interaction between MDP and hydroxyapatite. Many studies have confirmed that this unique nanolayering structure contributes to the longterm bonding durability of the hybrid layer and protects it from hydrolytic degradation 14,17,18) .…”
Section: Introductionmentioning
confidence: 92%
“…Preparation of experimental one-step adhesive EX-15 adhesive was used in this study 9,19) . It consisted of a base monomer, catalysts, inhibitor, filler, acetone, and water.…”
Section: Synthesis Of Mdp-ca Saltsmentioning
confidence: 99%
“…This is important because the MDP-Ca salt produced is embedded within the created adhesive layer and may cause the latter to degrade during the aging period. In a report by Takahashi 19) , dentin developed a greater amount of MDP-Ca salt than enamel and showed a greater reduction in bond strength than enamel after thermocycling. It was also found that reduction in dentin bond strength increased with an increase in the amount of MDP-Ca salt produced, in contrast to enamel bond strength which remained unchanged.…”
Section: Introductionmentioning
confidence: 97%